Investigating the factors affecting the development of digital innovations in Zimbabwe's SMEs - Vakirayi, Tafara (Department of Information Systems, 2021)
This study set out to investigate the factors affecting digital innovation development, and the relationship between these factors in the context of Small and Medium Enterprises in Zimbabwe. The research is founded on the seminal work of other scholars who have worked tirelessly to bring understanding to the contemporary phenomenon that is digital innovation. Unfortunately, SMEs in developing countries remain an under-researched and marginalised group – a gap which this explanatory research is intended to cover. The research is curious about the types of digital innovations that occur in Zimbabwe's SMEs, the factors affecting development of these digital innovations and areas of ameliorative action for improving the digital innovation performance of SMEs. The research is guided by a conceptual model developed through a literature review and utilises both quantitative and qualitative methods to analyse data which was collected from SME business owners, managers and partners. Although there is evidence of digital innovation in the country, the study establishes that both the innovative capacity and performance of SMEs is very low. Additionally, the results also point to a deliberate tendency to suppress the introduction of digital products by some businesses due to the prevalent market demands. Other notable outcomes include the impact of constrained financial resources on digital innovation performance, lack of knowledge management frameworks and more critically a general lack of understanding on what digital innovation is about. It was also established that culture, firm demographics and industry impact a firm's digital innovation capacity significantly while the market and opportunities for external collaboration is a significant moderator of the relationship between digital innovation capacity and performance. Fundamentally, this empirically grounded study represents a timely approach to technology, innovation, and intellectual integration which can be continuously enhanced to improve the narrative and comprehension on digital innovation especially in developing countries.